PENGARUH MODEL PROJECT BASED LEARNING DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR MENGGAMBAR BENTUK SISWA JURUSAN KRIYA KAYU SEKOLAH MENENGAH KEJURUAN NEGERI 8 PADANG - LIZA SARTIKA, Dr. Ramalis Hakin, M.Pd., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2017)
This study aims to assess whether student learning outcomes in learning to draw a form that is taught through a project based learning model is different from student learning outcomes taught through conventional model in class X SMKN 8 Padang. The hypothesis tested in this study is the result of learning to draw a form that is taught with the model of learning based learning differ significantly with student learning outcomes in learning to draw a form that is taught with the conventional model in class X SMKN 8 Padang.To answer the above problems, this research uses quasi-experimental quantitative research type (quasi experimental), with sample determination using random sampling technique in X grade students of wood craft skill of SMKN 8 Padang. The class chosen as the research sample is class X.2 as the experimental class and class X.1 as the control class. Data collection is done through early knowledge test instruments, test result learning instruments, and practice tests. The tests used need to be seen first of the difficulty index, distinguishing power, and reliability. Data analysis technique is done is descriptive processing stage, inductive analysis processing stage consisting of; Normality test and homogeneity test, and phase of hypothesis testing that is different test using (independent sample t test).The results showed that the results of learning students in learning to draw a form that is taught with a model based learning different from student learning outcomes in learning to draw a form that is taught with a conventional model in class X SMKN 8 Padang. Based on hypothesis test that tcount = 9,392 and significant 0.000 with error level equal to 0,05 (5%), hence Ho refused and Ha accepted.Based on the results of the above research, it can be concluded that the use of project based learning model has an effect on the improvement of learning outcomes in the learning of drawing the form.Keywords : Project Baset Learning and Early Knowledge Nowledge on Learning Results Drawing Form